Intracranial management of HER-2 overexpression breast cancer with extensive volume or symptomatic brain metastases - Li, Juan; Zhen, Junjie; Ai, Ruyu; Lai, Mingyao; Wang, Hui; Cai, Linbo (Frontiers in Oncology, 2024)
Objective: This study aimed to evaluate the impact of high intracranial burden and symptomatic presentation of brain metastases on treatment outcomes in patients with HER-2 positive breast cancer. Through a retrospective analysis, we explored the intracranial responses following the application of HER-2 targeted therapy alone or in combination with other modalities and further elucidated the relationship between treatment efficacy, intracranial progression-free survival (PFS), overall survival (OS), and the burden of intracranial lesions and symptomatic presentations.A retrospective analysis was conducted on cases of HER-2 overexpressing breast cancer patients with brain metastases. Clinical records were reviewed to extract patient demographics, treatment modalities, and intracranial disease characteristics. Intracranial tumor burden was quantified at diagnosis and post-initial treatment. High intracranial tumor burden was defined as either total metastatic volume >15 cc, or the largest lesion >3 cm. Responses were assessed using established criteria. The correlation between intracranial disease parameters and intracranial progression-free survival (PFS) and overall survival (OS) was determined.The study comprised 65 patients with HER-2 overexpression breast cancer and brain metastases. Symptomatic presentation was observed in 69.2% of patients at the diagnosis of brain metastases. Treatment with HER-2 target therapy alone or in combination with other modalities resulted in substantial intracranial responses, with 81.5% achieving at least a partial response at 3 months from therapy initiation. Median intracranial PFS and OS for patients with high intracranial burden were 9 and 22 months, respectively. Patients with high intracranial burden and symptomatic presentation at diagnosis demonstrated worse PFS and OS to those with lower burden and absence of symptoms (p < 0.05 for each).Her-2 overexpressing breast cancer and brain metastases face significant challenges, particularly those with high intracranial tumor burden, which correlates with poorer outcomes and higher incidence of leptomeningeal metastasis. Most patients responded positively to initial therapies, especially anti-HER-2 treatments combined with radiotherapy. Larger tumors necessitated more comprehensive treatment approaches, such as WBRT and SRS. Key factors influencing intracranial tumor control included the Ki-67 index, intracranial tumor burden, and continuous use of HER-2 targeted therapy post-diagnosis.